(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 1998)
The Muslim Missionary Society Singapore (Jamiyah), is one of the oldest Muslim organisations in Singapore. It is a da'wah organisation whose membership is open to all Muslims. It conducts expansive da'wah activities in which it caters for the needs of the Muslims and spreads the teachings of Islam to non-Muslims with a view to making them embrace Islam.